Folic acid and diseases - supplement it or not? - Liew,Siaw-Cheok (2016)
SUMMARY Introduction: folic acid is a water soluble vitamin, which is synthetically-produced and found in fortified foods and supplements. Folate is found naturally in plants, such as the dark green leafy vegetables. Folate is not synthesizedde novo by humans, therefore the daily requirements are met from the dietary intake of folic acid supplements or food rich in this vitamin. Folate deficiency could lead to numerous common health problems. Hyperhomocysteinemia and the possibility of malignancy developments are the long term consequences of this deficit albeit contradictory findings on these claims. Methods: the articles included in this review focused on recent updated evidence-based reports and meta-analyses on the associations of the serum folate/folic acid and the various diseases found globally. Results: the benefit of folic acid supplementation in the pre-conception period for the prevention of neural tube defects (NTDs) was well established and it was suggested that counseling sessions should be given to women with previous pregnancies affected by NTDs. However, supplementation of folic acid and its medicinal effects in the treatment of other diseases were contradictory and unclear. Conclusion: more detailed investigations into the health benefits of folic acid are needed before it could be recommended for supplementation, treatment or prevention of some of the diseases discussed in this review.